Vibration Measurement Method using 3 Accelerometer CMCP770A on Beam Cylinder with Fix-Fix Support and Double Selenoid - Badri, Muftil; Junianto, Fajar Dwi (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2018)
Vibration occurs due to excitation both from within and from outside the system, but the effect of vibration is very dependent on the excitation frequency and the elements of the vibration system itself. The purpose of this research is to find out the natural frequency value of the test specimens using accelerometer as a result of 2 selenoids with the same frequency as the fix-fix. The natural frequency was measurement of the cylinder beam rod with fix-fix pedestal. Four points of the test were given by using a double solenoid with the same frequency given on beam rod by varying the test point, then measured using 3 accelerometers and measured data then processed using data acquisition DT8837 through Quick DAQ program. The natural frequency of the beam cylinder rod can be detected by testing by using an excitation shaker or selenoids which in the beam cylinder rod is given disturbance by giving the excitation then recorded using accelerometer then processed using the data acquisition so that the frequency value of the beam rod is obtained. It was found that the processing of vibration analysis using the FFT process is used to find the frequency components of the mixed and hidden signal by noise in the time history signal. Natural frequency value is very important to know because if not known when designing a tool if not known natural frequency will harm the tool because if the tool vibrates about the natural frequency.